Paramedian incisional complications after prophylactic laparoscopy‐assisted gastropexy in 411 dogs. (8th December 2019) - Baron, Jessica K.; Casale, Sue A.; Monnet, Eric; Mayhew, Philipp D.; Runge, Jeffrey J.; Follette, Christelle M.; Phipps, Kevin; Powell, Margaret E.; Reczynska, Alicja I.; Squire, Nathan T.; Barton, Bruce A.; Berg, John
Abstract: Objective: To determine the frequency and types of paramedian incisional complications after prophylactic laparoscopy‐assisted gastropexy (LAG) in dogs and to evaluate potential risk factors for complications. Study design: Multi‐institutional retrospective study. Animals: Client‐owned dogs (N = 411). Methods: Records for dogs that underwent single‐incision–port laparoscopy‐assisted gastropexy (SIPLAG) or multiple‐port laparoscopy‐assisted gastropexy (MPLAG) at five veterinary referral hospitals were reviewed. Information regarding signalment, surgical procedures, perioperative care, and incisional complications was collected. Follow‐up information was obtained by review of medical records and/or communication with owners. Potential risk factors for complications were examined statistically. Results: Paramedian incisional complications were observed in 78 of 411 (19%) dogs. The most common complication was seroma formation, which occurred in 51 (12.4%) dogs. Surgical site infections were observed in 16 (3.9%) dogs, and dehiscence or development of excessive scar tissue at the incision site were each observed in nine (2.2%) dogs. Complications resolved with conservative treatment in 75 of 78 (96.2%) dogs and with surgical treatment in three of 78 (3.8%) dogs. The odds of complications were approximately twice as high in dogs undergoing SIPLAG than in dogs undergoing MPLAG (odds ratio, 2.03; P = .006). Conclusion: Minor paramedian incisional complications, particularly seroma formation, were frequently observed after LAG. Most complications were successfully managed conservatively. Single‐incision–port laparoscopy‐assisted gastropexy was associated with a higher complication rate compared with MPLAG. Clinical significance: Owners should be informed that there is a relatively high rate of minor paramedian incisional complications after LAG. The risk of complications appears to be higher for SIPLAG than for MPLAG.